Comparative performance of the EuroQol EQ-5D-5L and the CDC healthy days measures in assessing population health - Maryna Derkach; Fatima Al Sayah; Arto Ohinmaa; Lawrence W. Svenson; Jeffrey A. Johnson (SpringerOpen, 2022)
Abstract Objectives To examine the comparative performance of EuroQol EQ-5D-5L and Center for Disease Control Healthy Days measures in assessing population health. Methods Using data from 2014 Alberta Community Health Survey, a cross-sectional population-based survey (N = 7559), conducted in Alberta, Canada, we examined construct validity of the measures as indicators of population health. Differences in EQ-5D-5L index score, visual analogue scale (EQ-VAS), and CDC unhealthy days index across socio-demographic subgroups were tested by Mann-Whitney and Kruskal-Wallis tests using known-groups approach. Results EQ-5D-5L and CDC Healthy Days provided comparable assessments of population health in this sample. Both measures discriminated between subgroups defined by self-perceived health status, level of education, and material deprivation. The discriminative ability of CDC Healthy Days was limited in capturing variability in health among age groups compared to the EQ-5D-5L. Among participants who reported 0 unhealthy days, the proportion of those with level 3 problems in pain/discomfort varied from 1.1% for participants aged 18-24 to 19.2% for those over 75 years. Conclusions EQ-5D-5L demonstrated better construct validity than CDC Healthy Days in assessing health in a population-based sample of adults.